Determination of time-dependent uncertainty of the total solar irradiance records from 1978 to present - Fröhlich Claus (Journal of Space Weather and Space Climate, 2016)
Aims. The existing records of total solar irradiance (TSI) since 1978 differ not only in absolute values, but also show different trends. For the study of TSI variability these records need to be combined and three composites have been devised; however, the results depend on the choice of the records and the way they are combined. A new composite should be based on all existing records with an individual qualification. It is proposed to use a time-dependent uncertainty for weighting of the individual records.